The Role of the Comprehensive Economic Partnership Agreement (CEPA) and Investment in Indonesia’s Economic Diplomacy - Budiman, Imam; Abdurrahman, Bulbul; Aradea, Masayu Fatimah Azmi (RMPI-BRIN, 2025)
This article examines how Indonesia mobilizes economic diplomacy through Comprehensive Economic Partnership Agreements (CEPAs) to attract foreign investment and strengthen economic resilience. While CEPAs have proliferated as “deep” trade frameworks that extend beyond tariffs to services, standards, and investment provisions, evidence on how they deliver real-economy outcomes remains mixed. Adopting a qualitative, multiple–case design, the study synthesizes secondary sources—policy texts, official reports, and scholarly literature—and employs document analysis and process tracing to identify the mechanisms through which CEPA commitments are translated into performance. Findings indicate that four pathways—credibility signaling, rule harmonization, value-chain integration and aftercare alignmen are associated with export diversification and improved conditions for greenfield investment. These effects, however, are contingent on sub-national implementation capacity, regulatory coherence across agencies, and exposure to geoeconomic risks The study contributes by shifting the evaluation of CEPAs from “agreement presence” to “mechanisms under identifiable domestic conditions,” and it offers actionable recommendations: professionalize investment facilitation and aftercare, prioritize standards interoperability, and embed risk-management provisions in digital and investment chapters. Limitations stem from reliance on secondary data; future research should incorporate firm-level microdata to test mechanisms causally.